The Use of Gestures in Jumanji Movie: œWelcome to the Jungle - Siregar, Permata Surya; Hartati, Rita (Universitas Negeri Medan, 2024)
The aim of the study is to analyze the gestures of a groups of friends and the realization basen on the context in the mocieand culture, and how the gesture occurred in the movie. The description consists of (1)what kind of gesture used in Jumanji MovieœWelcome to The Jungle; (2) how the realization the context in the movie; (3) how arethe gesture occurred in Jumanji Movie œWelcome to The Jungle. This study useddescriptive qualitative method which is conducted to describe and analyze the gesturesused in the movie. The main theory is the kind of gestures by McNeil (2005). The dataanalysis requires the process of reducing data, dispalying data and consulting. The resultshows that this study has found 47 kinds of gestures which are used by the maincharacters in the movie. They are There are four types of gestures in the movie JumanjiWelcome to The Jungle (2017), as the researcher has done in the analysis. There are 47records found. There are 14 (30%) data as iconic gestures, 18 (38%) data as metaphorgestures, 13 (28%) data as deictic gestures, and 2 (44%) data as beat gestures. Eachgesture has their own meaning in context of the film and cultural context, for exampledeictic type, using the index finger to point in a different direction can be interpreted asa gesture to indicate and emphasize that the other person should look in the indicateddirection.